Managing Risk in the Digital Era: A Generational Approach-Z on Personal Risk Management - Amelia Setiawan; Samuel Wirawan; Hamfri Djajadikerta; Sandra Faninda (Universitas Hayam Wuruk Perbanas, 2024)
Risk management should be applied not only at the corporate level but also on a personal level. As technology becomes increasingly integral to daily life, implementing personal risk management in digital activities warrants examination. This study explores personal risk management within the context of online shopping. It investigates factors influencing personal risk management, including privacy concerns, perceived security threats, and internet self-efficacy. The study focuses on individuals from Generation Z, the first generation to grow up in a fully digital environment. Data were collected through online questionnaires, yielding 972 responses, of which 466 were analyzed further. The data were processed using SEM-PLS. The findings indicate that privacy concerns, perceived threats, and internet self-efficacy directly impact personal risk management, which in turn directly influences purchase intentions. This research offers valuable insights for regulators in crafting digital security regulations, for individuals in evaluating and enhancing their personal risk management strategies, for online retailers in designing robust data security measures, and for researchers as a contribution to the limited literature on this topic.